Utilization of coconut shell as fine aggregate in asphaltic concrete AC14 - Miron, Nurfatin Aqeela (2015)
Many previous studies have been done to carry out the waste material that can use to increase the performance of road pavement. Oil palm kernel shell, scrap tyre, and building waste material are the example of waste material that have been investigate to replace aggregate in road construction. Another alternative is to use coconut shell. Coconut shell is by product from agriculture activity. This study present the laboratory evaluation of aggregate properties on coconut shell and the performance of asphaltic concrete that use coconut shell to replace the fine aggregate. Only AC14 and 80/100 PEN bitumen were consider in this study. The investigations on the aggregate properties containing coconut shell are aggregate impact value (AIV) and specific gravity & water absorption. While, tests for performance of conventional asphaltic concrete AC14 and ACCS are volumetric properties, indirect tensile strength, resilient modulus and dynamic creep test. The result of the test shows that conventional asphaltic concrete AC14 give better volumetric properties than ACCS. For mechanical properties, replacement 10% of coconut shell as fine aggregate (ACCS10) shows better result than conventional asphaltic concrete AC14. Since this pavement has low strength, it will be only suitable for low traffic volume and at rural area.